Competências gerenciais: um estudo de caso com coordenadores de curso de pós-graduação stricto sensu da UFSM - Greco, Larissa Iop (2020)
This study aimed to analyze the managerial competencies necessary for the post of coordinator of strict sensu Postgraduate courses at the Federal University of Santa Maria, aiming to contribute with a training proposal. The methodology is classified as qualitative and quantitative in nature. As for its object, it is called descriptive and the research strategy as a case study. The data collection procedure was developed in three stages. The first step was through the analysis of documents of the studied institution and CAPES files. The second stage semi-structured interview with eight postgraduate course coordinators, who were chosen by means of a simple random sample, through a draw based on the CAPES concept (2017). The third step was the questionnaire, which was based on its first part on the author Quinn et al (2003) and Comin et al. (2017); and the second by the authors Yulk (1998) and Fleck (2008), being sent to the 59 coordinators of the strict sensu Course at UFSM via Googles Docs, obtaining a return of 25 questionnaires. The data were treated, through content analysis for the open questions, through analysis categories, summary tables and excerpts from the interview statements; and also through Excel Software and SPSS statistical program, for closed questions. As for the results, it is emphasized that the understanding of the competence word most cited by four coordinators was skills. And in relation to the expression managerial competences, he had several understandings such as: Postgraduate routines, associated with the position, innovation, management and skills. In addition, the fundamental competences most referred to in the coordinators' view to occupy a post as a strict sensu Postgraduate course coordinator were: knowledge, organization and interpersonal relationships. As for the questionnaires, the skills in relation to the role of the leaders that stood out the most were Coordinator (91.3%), Mentor (89.9%) and Monitor (88.1%). Regarding managerial behavior, the highlighted constructs were to inform (91.4%), to support (89.7%) and recognition (86.9%). Finally, given the suggestions regarding the training, the relevant were: the need for information exchange between the coordinators, specific training for skills, how to work with systems, strategic planning, how to manage people, more technical courses with greater workload, having a professional administration area assisting and a manual or booklet for the coordinator was also mentioned. Thus the final product to be proposed will be an Integrated Seminar for Exchanging Ideas, which will have space for the coordinators to talk to each other, training for new coordinators of the Post-Graduate strict sensu course and recycling for those already in charge.